2007
DOI: 10.1080/09670260601092364
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a differentially expressed gene in separate mating types of the dinoflagellateAlexandrium tamarense

Abstract: In this study, subtractive PCR was used to isolate a gene that is differentially expressed in the different mating-type cells of Alexandrium tamarense. After three rounds of subtractive PCR using cDNAs synthesized from mRNA of different matingtype cells, amplified PCR products were subcloned into a plasmid vector for construction of subtractive libraries. The dependence on mating type for different levels of accumulated mRNA in randomly selected library clones was confirmed by cDNA membrane array, amplified cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…haploid reductions via meiosis. That the LECA was sexual is no longer a matter of speculation/ debate as evidence of sex, and of genes exclusively involved in meiosis, has been found in all of the major eukaryotic radiations (Brawley and Johnson 1992;Ramesh et al 2005;Kobiyama et al 2007;Malik et al 2008;Phadke and Zufall 2009;Fritz-Laylin et al 2010;Lahr et al 2011;Peacock et al 2011;Vanstechelman et al 2013).…”
mentioning
confidence: 99%
“…haploid reductions via meiosis. That the LECA was sexual is no longer a matter of speculation/ debate as evidence of sex, and of genes exclusively involved in meiosis, has been found in all of the major eukaryotic radiations (Brawley and Johnson 1992;Ramesh et al 2005;Kobiyama et al 2007;Malik et al 2008;Phadke and Zufall 2009;Fritz-Laylin et al 2010;Lahr et al 2011;Peacock et al 2011;Vanstechelman et al 2013).…”
mentioning
confidence: 99%
“…1993; Parker ; Kobiyama et al . 2007). While Kremp and Anderson (2004) reported that the cell wall of gametes contained specific lectin binding structures that assisted in gamete fusion and conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…strain SGCH-03 (Nomaru 2005) and A. tamarense strain OFAT0105-8 (Kobiyama et al 2006), were used in the present study. Symbiodinium sp.…”
Section: Cell Culturementioning
confidence: 99%